Impact of media reporting of the september 11th events on the activities of the nonprofit islamic organizations in the united states / Hulayyil Muhisen S. Alomiry - S. Alomiry, Hulayyil Muhisen (2014)

(untitled)
This research explores the influence of the September 11, 2001 (9/11) attacks on nonprofit Islamic organizations with activities in the United States. The study employs discourse analysis to examine newspaper articles, interviews of leaders of these organizations, as well as data and figures released by these organizations. The articles were mainly taken from US media, namely CNN and Washington Post as representatives of the US media. Instruments of data collection about these organizations include, semi- structured interviews, a questionnaire, and an in-depth analysis of media materials, news reports and articles of CNN and Washington Post. Content analysis was used to analyze media articles and news stories. Data analysis reveals some important information such as the presumed serious negative impact on their organizations activities which include Da’wa activities, congregational religious services introducing Islam to non-Muslims, establishing mosques and Islamic centers. Political and other activities were also found to be deeply affected by the 9/11 events. In addition, events of 9/11 also negatively impacted the level of participation of Muslim youth and Muslim Scholars in the various activities arranged by these organizations. Also, the US government closely monitors the activities of these organizations. On the American media level, the results indicate that US media often projects negative views of the activities of the Islamic organizations based in America.The research ends up giving some suggestions and recommondations to enhance and re-vitalize the activities of the Islamic charity organizations.